La Auditoría Financiera y su influencia en la Gestión de las pequeñas empresas manufactureras del Régimen General del Impuesto a la Renta en la ciudad de Tarapoto. Año 2014 - Arana Ruiz, Erika Karina (2015)
The present research work was developed to determine if the financial audit influences the management of small manufacturing companies in the general regime of income tax in the city of Tarapoto; for which the methodology of scientific research and the survey technique was used to collect information from businessmen. The work in the conceptual theoretical part, was carried out with the information compilation from different sources such as previous thesis related to the subject, books, internet, etc; these contributions helped to consolidate the development of variables Financial Audit and Management small businesses, clarifying the importance of definitions and concepts related to the topic in question. As to fieldwork, the survey technique was used with the instrument the questionnaire, the same that consisted of 29 questions that allowed to know the current situation of small manufacturing enterprises in relation to the audit process. The information obtained it was tabulated and then to was processed graphically, allowing the interpretation of the results and hypothesis testing, in order to finish with conclusions and recommendations. Finally, the development of the thesis, led to the conclusion that the financial audit positively influences the management of small manufacturing companies of the general regime of income tax in the city of Tarapoto, as the managers of these companies consider it important application since it is a key to the development and growth of any company technique as gives possibilities for change and improvement.